Da molécula de DNA às proteínas: dinamizando o ensino por meio de materiais didáticos e ludicidade - Paes, Kelly Cristina (2019)
DNA is a leading molecule accountable for storing and transmitting genetic information. It is constantly mentioned by the media when it comes to genetic engineering, genome design, paternity testing, biotechnology, transgenic foods, recombinant ADN, cloning and, when studied in the classroom, arouses fascination in students. Though, those have trouble understanding their composition, organization and operation, in what it refers to replication, transcription and translation processes. Therefore, this work proposed a didactic sequence applicating problematization, discussion of articles, videos and a ludic kit “Unraveling the mysteries of ADN” built on felt, zipper and velcro pieces. Data collection was given through by pre- and post- questionnaires and observations of the proponent in the classroom. The didactic sequence was validated in 1st and 2nd grades on high school and the results showed that the students achieved a better understanding of the content using methodological diversity and playful tool, reflecting on learning. The students of the first year, who had not previously studied the subject, obtained expressive positive result in understanding, reaching up to 90% of correct answers in the questionnaires offered at the end of the whole didactic sequence and the kit. The 2nd year students, who had previously studied the subject in lectures, presented conceptual flaws that were resignified in the didactic sequence. The whole didactic sequence (together with the kit) was evaluated by the students in a positive way indicating its validity in relation to the clarification of the concepts covered. A Teacher’s Guide has been prepared allowing the construction of the kit and development of the didactic sequence.